Maqāṣid Al-Syarī'ah Al-Syāṭibī and Responsive Law: A Fair Formulation for Registering Guardians in the Marriage of Adopted Children - Mustofa, Bisri; Saifullah, Saifullah; Sudirman, Sudirman (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the practice of marriage guardian registration in adopted children's marriages in Mojokerto Regency and City, particularly regarding the validity of marriage guardianship between adoptive fathers and biological fathers, and to review the policies of Marriage Registrars (PPN) from the perspective of Maqāṣid al-Syarī'ah al-Syāṭibī and responsive legal theory. The research method used is descriptive qualitative with a normative-sociological legal approach. Data were obtained through interviews with PPNs at 21 Religious Affairs Offices (KUA) in Mojokerto Regency and City and a review of legal documents, such as Law Number 1 of 1974 concerning Marriage, Law Number 35 of 2014 concerning Child Protection, The results of the study indicate that the VAT policy in conducting the marriage of adopted children with the biological father as a guardian, even though the administrative document lists the adoptive father, is a form of responsive legal application. The policy is oriented towards the benefit (maslahah) as per the principles of Maqāṣid al-Syarī'ah which includes protection of religion (ḥifẓ al-dīn), descendants (ḥifẓ al-nasl), and soul (ḥifẓ al-nafs). However, administratively, the existing regulations have not accommodated this social reality, resulting in a normative vacuum. This study recommends a new legal formulation in the form of an additional article in the marriage registration regulations that authorizes the KUA (Office of Religious Affairs) to correct marriage certificates without going through two stages of court proceedings. This formulation is expected to provide legal certainty, justice, and benefits for the community and strengthen the integration between Islamic law and positive law in Indonesia.